Keragaman Genetik Kelapa Sawit (Elaeis guineensis Jacq.) Asal Angola Menggunakan Marka SSR - Sayekti, Urip; Widyastuti, Utut; Toruan-Mathius, Nurita (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTEffort to increase productivity and other elite characters in Indonesia oil palm breeding program is facing a problem because of the narrow genetic diversity. To broaden the genetic diversity, germplasm exploration has been done in Angola, Central Africa. The objective of this research was to assess the genetic diversity and population structure of Angola originated oil palm germplasm based on 20 SSR markers. The plant materials used were 27 accessions consisted of 136 palms planted in Riau, Sumatera. The DNA was isolated and amplified using PCR. Phylogeny analysis was constructed using Unrooted Neighbor-Joining by DARwin software 6.0.8. The result showed that polymorphic information content (PIC) value is 0.55 (0.17 to 0.75 for each locus) with 102 total number of alleles. Genetic diversity between individuals was higher compared to the genetic diversity within accessions or regions and between accessions or regions. Phylogenetic analysis of 27 accessions showed that accessions were divided into three main groups. Every group containing individuals originated from 5 spatial distribution regions. Principal coordinates analysis (PCoA) showed that accessions were distributed in one structure. Using more primers and samples to get more representative data is recommended for the following research.Keywords: allele, locus, germplasm, molecular marker, polymorphic